Persistence of human enteric viruses in artificial and human saliva - Sharon C. Kosgei; Olivia N. Birch; Justin C. Greaves (PLoS ONE, 2025)
Enteric viruses, such as Adenovirus 41 (AdV41) and Coxsackievirus B3 (CVB3), are significant contributors to gastrointestinal infections, particularly among young children and immunocompromised individuals. While fecal-oral transmission is the primary route of infection, emerging evidence indicates that saliva may also function as a reservoir for these viruses, posing a potential risk for oral transmission. Previous studies have primarily focused on the decay of viruses in aqueous matrices, like wastewater and freshwater, but the persistence of these viruses in human saliva remains underexplored. This study aimed to investigate the persistence of AdV41 and CVB3 in both human and artificial saliva under various conditions, including the presence of fecal particles and specific oral bacteria. Our findings demonstrated that human saliva significantly reduced viral stability compared to artificial saliva, with marked reductions in viral titers observed within 24–48 hours. Particularly, the presence of fecal particles in both saliva types extended CVB3 viral persistence, suggesting a protective effect due to particle adsorption. However, AdV41 demonstrated an opposite trend when in the presence of fecal particles, suggesting virus-specific differences in how particulate matter influences stability. Additionally, specific oral bacteria, such as Streptococcus mutans , significantly enhanced CVB3 stability, with a mean viral recovery of 23.2% of the viral titer after 24 hours in the presence of the bacteria compared to 0.7% in their absence ( p = 0.001). This study shows complex interactions between viruses, oral bacteria, and fecal particles within the oral environment, emphasizing the need for further research on oral viral persistence and transmission dynamics. Understanding these mechanisms behind viral persistence in saliva can inform public health strategies aimed at mitigating the risk of transmission.